(untitled) (Research Announcements "Heritage BG", 2025)
The current study analyzed the data on the presence of foreign military contingents and troops in the Balkans during the late 9th – mid-11th centuries. Particular attention is paid both to the information available in the written sources and to the material evidence (elements of armament) that prove to some extent the existence of military elements ‘external’ to Byzantium and the First Bulgarian Kingdom. The period under consideration was extremely dynamic in terms of military campaigns raids and mercenary activities in the lands along the Lower Danube. From the end of the 9th to the beginning of the 10th century the so-called late nomads, or more specifically Magyars and Pechenegs, began to cross south of the Danube. Some of them were used as mercenaries. The study also sheds light on the presence of troops and mercenaries from Northern Europe in the Balkan territories. In the second half of the 10th century, the Balkans became the object of raids mainly by the Varyago-Russians. It is about the campaigns of the Kievan prince Svetoslav I Igorevich (963 – 972) in the period 968 – 971 to the Bulgarian lands and Constantinople under the rule of the Byzantine emperor John Tzimiskes (969 – 976). A little more than a decade later, after the Christianisation of Kievan Rus in 988, Emperor Basil II (976 – 1025) recruited about 6,000 Varangians to form his guards and thus created the so-called ‘Varangian Corps’, personally responsible for guarding the Byzantine Emperor. Discoveries of northern European origin weaponry in the Balkans are associated with well-armed military contingents from the North and trade relations between the Varangians and Byzantium, which are also well-attested in Byzantine written sources. The study also traces the events and analyses the data (written and material) that we have about the massive late nomadic raids in the 11th century in the lands of the Lower Danube. References: Primary sources: Ataliata 1965: Ataliata, Michael. ‘Historia’. – Gratski izvori za balgarskata istoriya, No. 6, 159 – 197. Comnenae 1972: Comnenae, Anna. ‘Alexias’. – Gratski izvori za balgarskata istoriya, No. 8, 7 – 149. Diaconi 1964: Diaconi, Leonis. ‘Historiae’. – Gratski izvori za balgarskata istoriya, No. 5, 245 – 276. Kurze 1890: Kurze, Friedrich. ‘Reginonis abbatis prumiensis chronicon cum continuatione Treverensi’. Hannover. Likhachyov, Tvorogov 2012: Likhachyov, Dmitriy, Oleg Tvorogov. „Povest’ vremennykh let“. Saint Petersburg. Philosophi 1961: Philosophi, Leonis. ‘Tactica’. – Gratski izvori za balgarskata istoriya, No. 4, 166-174. Porphyrogenitus 1964: Porphyrogenitus, Constantinus. ‘De administrando imperio’. – Gratski izvori za balgarskata istoriya, No. 5, 198 – 220. Pselli 1965: Pselli, Michaelis. ‘Epistolae’. – Gratski izvori za balgarskata istoriya, No. 6, 119 – 128. Tsamakda 2002: Tsamakda, Vasiliki. The Illustrated Chronicle of Ioannes Skylitzes in Madrid. Leiden. Zonarae 1968: Zonarae, Ioannis. „Istoriya“. – Gratski izvori za balgarskata istoriya, No. 7, 149 – 208. Secondary sources: Atanasov, Stoychev, Doncheva 2004: Atanasov, Georgi, Stanimir Stoychev, Stela Doncheva. Tri sabi ot rannoto balgarsko Srednovekovie (Novi postapleniya v RIM – Shumen). – Izvestiya na istoricheskiya muzey Shumen, No. 12, 73 – 77. Atanasov 2018: Atanasov, Georgi. Otnovo za Rusko-varyazhskite kultovi bradvichki na Dolen Dunav – Corrigenda et addenda (po povod novi nahodki ot Drastar/Silistra). – Prinosi kam balgarskata arheologiya, No. 8, 221 – 234. Bonev 1983: Bonev, Stoycho. Hudozhestvenata rezba varhu kost – vrazki i vliyaniya s drugite prilozhni tehniki prez IX v. – Preslav, No. 3, 149 – 159. Bonev 1993: Bonev, Stoycho. Arhitekturen kompleks v Preslav. – Preslav, No. 4, 56 – 78. Doncheva-Petkova 1999: Doncheva-Petkova, Lyudmila. Odartsi. Selishte ot Parvoto balgarsko tsarstvo. 1. Sofia. Doncheva, Totev (in print): Doncheva, Stela, Boyan Totev. Sabya ot mestnostta Fiseka, Shumensko. Fehér 1938: Fehйr, Géza. Voennoto delo na prabalgarite. Sofia. Georgiev 1986: Georgiev, Pavel. Nahodka ot vikingsko vreme. – Muzei i pametnitsi na kulturata, No. 3, 19 – 23. Georgiev 2008: Georgiev, Pavel. Kalap za monetovidni znatsi (brakteati) s psevdokuficheski nadpis ot Pliska. In: Yubileen sbornik v chest na 100-godishninata ot rozhdenieto na d-r Vasil Haralanov (1907 – 2007). Shumen, 353 – 364. Ivanov 2016: Ivanov, Mario. Vikingska kultova bradvichka-amulet ot Sofiya. – Godishnik na Natsionalniya arheologicheski muzey, No. 13, 259 – 261. Ivanov 1994: Ivanov, Plamen. Srednovekovni boyni bradvi ot Vrachansko. – Izvestiya na muzeite v Severozapadna Balgariya. No. 22, 65 – 79. Ivanov, Ivanov 2015: Ivanov, Rumen, Rosen Ivanov. Pogrebalni obredi na pechenezi i kumani po balgarskite zemi (XI – XIII v.). Plovdiv. Kaminski, Kaminsaya-Tsokur 1997: Kaminski, Vladimir, Irina Kaminskaya-Tsokur. Vooruzhenie plemen Severnogo Kavkaza v rannem srednevekovye. V: Istoriko-arheologicheskiy alymanah. Vыp. 3 (ed. Rauìf Munchayev). Armavir, 61 – 69. Kanev 2002: Kanev, Ivaylo. Novopostapila rannosrednovekovna sabya vav fondovete na Natsionalniya istoricheski muzey. In: Acta Musei Varnensis, I (eds. Valeri Yotov, Vesselin Nikolov, Vladimir Slavchev). Varna, 119 – 122. Kirpichnikov 1966: Kirpichnikov, Anatoliy. Drevnerusskoye oruzhiye. Vyp. 1. Mechi i sabli IX – XIII vv. – Arkheologiya SSSR. Svod arkheologicheskikh istochnikov, E1-36. Moskva-Leningrad. Konstantinov 2011: Konstantinov, Konstantin. Kam vaprosa za vaorazhenieto v Parvoto balgarsko tsarstvo. In: Istorikii. Tom 4. Nauchni izsledvaniya v chest na profesor din. Ivan Karayotov po sluchay negovata 70-godishnina (eds. Ivan Yordanov, Rositsa Angelova, Konstantin Konstantinov, Todor Todorov). Shumen, 293 – 298. Makarov 1992: Makarov, Nikolay. Drevnerusskiye amulety-toporiki. – Rossiyskaya arkheologiya, No. 2, 41 – 56. Matanov 2022: Matanov, Hristo. Srednovekovnite Balkani. Istoricheski ochertsi. Sofia. Minaeva 2013: Minaeva, Oksana. Vikingski nahodki na Balkanite: Funktsiya, semantika, stilova interpretatsiya. Sofia. Parushev 1999: Parushev, Srednovekoven mech ot Popovsko (kraya na X – nachaloto na XI vek). – Аrchaeologia Вulgarica, No. 1, 31 – 32. Popov 2018: Popov, Stoyan. Chetiri mecha ot Natsionalniya arheologicheski muzey v Sofiya. In: Acta Musei Varnensis, Х-2. Voenni ekspeditsii, vaorazhenie i snaryazhenie (antichnost i srednovekovie) (ed. Igor Lazarenko). Varna, 137 – 142. Rabovyanov 2013: Rabovyanov, Deyan. Srednovekovni predpaziteli za mech ot Balgariya. – Prinosi kam balgarskata arheologia, No. 7, 99 – 114. Rabovyanov 2019: Rabovyanov, Deyan. Srednovekoven predpazitel za sabya i chast ot metalen obkov za nozhnitsa ot razkopkite na krepostta Hotalich do Sevlievo. In: Sevlievo i Sevlievskiyat kray. Arheologicheski prouchvaniya, Yubileen sbornik po sluchay chetirideset godini ot nachaloto na arheologicheskite razkopki na rannovizantiyskata i srednovekovna krepost pri grad Sevlievo (ed. Diana Koseva). Sevlievo, 123 – 130. Savenko, Sergey 1986: Savenko, Sergey. Эtnokulyturnaya harakteristika bogatыh pogrebeniy kontsa XI – pervoy polovinы XII vv. mogilynika Kolytso-Gora. In: Эtnokulyturnыe problemы bronzovogo veka Severnogo Kavkaza (ed. Tamerlan Turgiyev). Ordzhonikidze, 75 – 92. Sirakov 2018: Sirakov, Nikolay. Mech i boyna bradva – skandinavsko orazhie ot fonda na muzeya v Sliven. In: Acta Musei Varnensis, Х-2. Voenni ekspeditsii, vaorazhenie i snaryazhenie (antichnost i srednovekovie) (ed. Igor Lazarenko). Varna, 143 – 146. Stanilov 1999: Stanilov, Stanislav. Starobalgarski kolanni garnituri za orazhiya ot Severoiztochna Balgariya. – Arheologicheski vesti, No. 1, 33 – 40. Tapkova-Zaimova 1976: Tapkova-Zaimova, Vasilka. Dolni Dunav - granichna zona na Vizantiyskiya zapad. Sofia. Yotov 1992: Yotov, Valeri. Sabya ot rannosrednovekovnoto selishte do s. Debrene, Dobrichko. - Dobrudzha, No. 9, 141 – 145. Yotov 2003: Yotov, Valeri. Nakraynitsi ot grupata „germanski chetirinog zvyar“ v „zhivotinskiya stil na Baltiysko more“. - Pliska-Preslav, No. 9, 132 – 135. Yotov 2004: Yotov, Valeri. Vaorazhenieto i snaryazhenieto ot balgarskoto Srednovekovie (VII–XI vek). Sofia. Yotov 2011: Yotov, Valeri. Byzantine Time Swords (10th-11th centuries) in Romania. – Studia Universitatis Cibiniensis (Series Historica), No. 8(1), 35 – 45. Yotov 2014: Yotov, Valeri. Vizantiyskiyat mech (VII – XI vek). In: Tsar Samuil († 1014) v bitka za Balgariya. Sofia, 91 – 103. Yotov 2015: Yotov, Valeri. Predpazitel na mech ot Pliska. – Pliska-Preslav, No. 11, 233 – 241. Zlatarski 1971: Zlatarski, Vasil. Istoriya na balgarskata darzhava prez srednite vekove. Istoriya na Parvoto balgarsko tsarstvo. Ot slavyanizatsiyata na darzhavata do padaneto na Parvoto balgarsko tsarstvo 1(2). Sofia. Zlatkov 2014: Zlatkov, Metodi. Sabya ot Yarebitsa, Sabya ot rayona na Pliska, Aplikatsiya na remak za okachvane na sabya, Varna, № 4938, Aplikatsiya na remak za okachvane na sabya, Varna, № 5000, Mech ot Opaka, Mech ot Sliven, Mech ot Gradeshnitsa, Брадва от Стан, Bradva ot Neykovo. In: Tsar Samuil († 1014) v bitka za Balgariya (ed. Lyudmil Vagalinski). Sofia, 138 – 139, 140 – 141, 142 – 143, 162 – 163, 164 – 165, 166, 175 – 176, 176 – 177. Alexander 2001: Alexander, David. Swords and Sabers During the Early Islamic Period. – Gladius, No. 21, 193-220. Dienes 1972: Dienes, Istvan. The Hungarians Cross the Carpathians. Budapest. Doncheva, Totev 2011: Doncheva, Stela, Boyan Totev. A New ‘Hungarian’ Type Saber from the Outskirts of Pliska. In: Avars, Bulgars and Magyars on the Middle and Lower Danube: Proceedings of the Bulgarian-Hungarian Meeting, Sofia, May 27 – 28, 2009 (eds. Lyudmila Doncheva-Petkova, Csilla Balogh, Attila Türk). Sofia – Szeged, 121 – 124. Fettich 1937: Fettich, Nándor. A honfoglaló magyarság fémművessége. Budapest. Fillitz 1971: Fillitz, Hermann. Die Wiener Schatzkammern. Katalog der weltlichen und geistlichen Schatzkammer. Führer durch das kunsthistorische Museum. 2. Vienna. Kamburov 2021: Kamburov, Samuil. Early Medieval Weapons for Close Combat of North European Origin Found within Present-day Bulgarian Territory. – Bulgarian e-Journal of Archaeology Supplements, No. 8, 89 – 116. Oakeshott 1960: Oakeshott, Ewart. The Archaeology of Weapons: Arms and Armour from Prehistory to the Age of Chivalry. Woodbridge. Pálóczi-Horváth 1989: Pálóczi-Horváth, András. Pechenegs, Cumans, Iasians: Steppe Peoples in Medieval Hungary. Budapest. Petersen 1919: Petersen, Jan. De norske vikingesverd: en typologisk-kronologisk studie over vikingetidens vaaben. Viden-skapsselskapets Skrifter. II, Hist.-Filos. Klasse. No1. Kristiania (Oslo). Popa 1984: Popa, Radu. Knaufkrone eines wikingerzeitlichen Prachtschwertes von Păcuiul lui Soare. – Germania, No. 62, 425 – 431. Popov 2016: Popov, Stoyan. Early Mediaeval Sword and Sword-pommels from North Eastern Bulgaria. – Русский сборник, No. 8(1), 109 – 112. Rabovyanov 2011: Rabovyanov, Deyan. Early Medieval Sword Guards from Bulgaria. – Archaeologia Bulgarica, No. 15(2), 73 – 86. Schulze-Dörrlamm 1984: Schulze-Dörrlamm, Mechthild. Das ungarische Kriegergrab von Aspres-lès-Corps. Untersuchungen zu den Ungarneinfällen nach Mittel, West und Südeuropa (899 – 955 n.Chr.) mit einem Exkurs: Zur Münzchronologie altungarischer Gráber. – Jahrbuch des Römisch Germanischen Museums in Mainz, No. 31, 473 – 514. Spinei 2022: Spinei, Victor. The Great Migrations in the East and South East of Europe from the Ninth to the Thirteenth Century. Amsterdam. Vinogradov 1983: Vinogradov, Vitaliy. Altungarische Parallelen zu einigen Grдbern des alanischen Grдberfeldes bei Martan-Cu. – Acta Archaeologica Academiae Scientiarum Hungaricae, No. 35, 211 – 220. Yotov 2018: Yotov, Valeri. Data about Northmen`s Presence in the Lower Danube area. – Studia Romana et Mediaevalia Europaensia, No. 13, 467 – 484. Yotov, Valeriev, Totev 2018: Yotov, Valeri, Yoto Valeriev, Boyan Totev. Traces of Scandinavian Warriors’ Presence on the Balkans. – Acta Musei Varnaensis, No. 10(1), 103 – 122. Yotov 2008: Yotov, Valeri. A Note on the ‘Hungarian Sabers’ of Medieval Bulgaria. In: The other Europe in the middle ages. Avars, Bulgars, Khazars, and Cumans (ed. Florin Curta). Leiden – Boston, 327-338. Yotov 2008: Yotov, Valeri. The Vikings on the Balkans (10th-11th centuries). Strategic and tactical changes. New archaeological data on the weaponry. – Arhaeologia Baltica, No. 8, 321 – 327. Yotov 2011: Yotov, Valeri. Byzantine Time Swords (10th-11th centuries) in Romania. – Studia Universitatis Cibiniensis (Series Historica), No. 8(1), 35 – 45. Sites: Der „Sábel Karls des Großen“ – https://www.europeana.eu/en/item/15502/SK_WS_XIII_5 (29.05.2023)